2014
DOI: 10.4081/hr.2014.5554
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for a Pediatric-Inspired Approach in the Adolescent and Young Adult Population with Acute Lymphoblastic Leukemia, with a Focus on Asparaginase Treatment

Abstract: In the last two decades great improvements have been made in the treatment of childhood acute lymphoblastic leukemia, with 5-year overall survival rates currently approaching almost 90%. In comparison, results reported in adolescents and young adults (AYAs) are relatively poor. In adults, results have improved, but are still lagging behind those obtained in children. Possible reasons for this different pattern of results include an increased incidence of unfavorable and a decreased incidence of favorable cytog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The 5year eventfree survival of ALL in Europe is currently 86.3%, 4 and paediatric protocols introduced for adults with ALL were more effective than conven tional protocols. [5][6][7] Notably, some paediatric rheumatic diseases can be as aggressive and fatal as malignant diseases if left untreated; for example, stimulator of interferon genes protein (STING)associated vasculopathy in infancy (SAVI), and chronic infantile neurological cutaneous articular syndrome (CINCA, also known as neonatal onset multiinflammatory disease [NOMID]). [8][9][10] The clinical presentation of ALL and juven ile idiopathic arthritis (JIA), the two most common diseases in paediatric onco logy and paediatric rheumatology, is often very similar (Table 1), with frequent leg pain and arthralgia, and the referral of new ALL cases from paediatric rheumatology clinics to paediatric oncologists is not uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…The 5year eventfree survival of ALL in Europe is currently 86.3%, 4 and paediatric protocols introduced for adults with ALL were more effective than conven tional protocols. [5][6][7] Notably, some paediatric rheumatic diseases can be as aggressive and fatal as malignant diseases if left untreated; for example, stimulator of interferon genes protein (STING)associated vasculopathy in infancy (SAVI), and chronic infantile neurological cutaneous articular syndrome (CINCA, also known as neonatal onset multiinflammatory disease [NOMID]). [8][9][10] The clinical presentation of ALL and juven ile idiopathic arthritis (JIA), the two most common diseases in paediatric onco logy and paediatric rheumatology, is often very similar (Table 1), with frequent leg pain and arthralgia, and the referral of new ALL cases from paediatric rheumatology clinics to paediatric oncologists is not uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of most, if not all of these, increases with age. 18,42 As a result of these toxicity concerns and general lack of use in traditional adult ALL regimens, the benefit of vincristine and asparaginase in ALL outcomes is not as appreciated in adults as in children. 48 It should be noted that when treated with typical adult protocols, the AYA population represents only a small number of total patients being treated.…”
Section: Current Treatment Strategiesmentioning
confidence: 99%
“…Its mechanism of action is to induce apoptosis of leukemic cells as a result of the cells' inability to undergo proper protein biosynthesis due to the lack of extracellular asparagine. 41,42 Studies in which intensive rounds of asparaginase are used in induction and intensification have demonstrated significant benefits in EFS and overall disease cure rates. 42 In addition, a series of clinical trials conducted through the Dana Farber Cancer Institute (DFCI) has clearly demonstrated the range of toxicities, the importance of frequent exposure, and that more doses improve outcomes.…”
Section: Current Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in AYAs less intensive treatments (especially lower cumulative doses of drugs such as asparaginase, corticosteroids and methotrexate) and longer gaps between courses of chemotherapy are planned compared to those in children. There is considerable evidence from retrospective analyses that treating AYAs with a pediatric protocol may improve clinical outcomes compared with treatment adopted in adult protocols(Rizzari et al, 2014). Treatment of older adults with T-ALLThe hyper-CVAD (cyclophosphamide, vincristine, Adriamycin, and dexamethasone alternating with high dose methotrexate and cytarabine) regimen is considered intensive and in spite of this is reasonably well tolerated in fit older individuals.…”
mentioning
confidence: 99%